Project Planning with Limited Resources and as Part of a Project Portfolio - Bozena GAJDZIK; Stanislaw CHMIST; Piotr STARON (Communications of International Proceedings, 2022)
What we found missing from the literature was a holistic view of project planning with limited resources and as part of a project portfolio. Participant observation was the primary research method. The authors relied on the analysis of the literature on the subject, confronting it with the results of observation and own reflections. Methodology of project planning includes both simple methods and very complicated techniques. There are no universal methods when we make project plan within the confines of multi-project environment which divides resources. Knowledge of methods is useful when we select a proper technique for a specific application.
Keywords: project planning; project portfolio; limited resources